Bank Loan Classification and Provisioning Practices in Selected Developed and Emerging Countries - Laurin, Alain; Majnoni, Giovanni (Washington, DC: World Bank, 2013)
This report reviews loan classification and provisioning practices in a broad sample of countries that differ in size, location and level of financial development. The survey conducted for the report compares the regulatory approaches adopted by industrial and emerging economies, and is intended to complement other sources of information that focus exclusively on either industrial or developing countries. It covers classification of individual and multiple loans, treatment of guarantees, collateral and restructured loans, bank loans review processes, loan loss provisioning, tax treatment of loan loss provisions, disclosure standards, and external auditors' role. Differences in provisioning and classification approaches have often made difficult a comparison of bank and banking system weaknesses across regulatory regimes. Poor classification and provisioning practices have led to solvency ratios that gave a false sense of security, as occurred when seemingly adequately capitalized financial systems failed in the 1990s. Successful regulatory harmonization therefore requires a set of minimum standards for loan classification that is grounded in sound risk management practices, but that is also sufficiently general to recognize differences in national economic and legal environment. The evidence this report provides is intended to contribute to this difficult task.